A study of film thickness and hydrodynamic entrance length in liquid laminar film flow along a vertical tube. Issue 6 (22nd January 2018) - Gao, Hongxia; Luo, Xiao; Cui, Ding; Liang, Zhiwu; Hu, Xiayi; Hartono, Ardi; Svendsen, Hallvard F.
Abstract : The liquid film thickness and hydrodynamic entrance length in a vertical tube was studied experimentally and numerically. Measurements using distilled water, 30 wt % MEA and 40 wt % sugar solutions were carried out to investigate the effects of liquid flow rate on the formation of the liquid film. The experimental results validate the new Navier‐Stokes based equation in cylindrical coordinates (Eq. 16) and the volume of fluid (VOF) model giving a competitively high prediction of the liquid film thickness especially in the low Reynolds number region. In addition, a new empirical model and an improved minimal surface model have been first proposed for calculation of the hydrodynamic entrance length, with a relatively reasonable average absolute relative deviation (AARD) of 3.03% and 6.83%, respectively. Furthermore, the effects of the hydrodynamic entry length on the gas–liquid interfacial area calculated by the improved minimal surface model were comprehensively studied, and can be ignored if the ratio of the liquid film length (y) and the hydrodynamic entrance length (λE ) is lower than 10. However, it should be noted that the hydrodynamic entrance length cannot be ignored in packed columns in which the liquid flow is very complex due to the packings with different structures and materials. © 2018 American Institute of Chemical Engineers AIChE J, 64: 2078–2088, 2018